A NEEDS ASSESSMENT FOR THE DEVELOPMENT OF THE LEARNING ASSESSMENT ABILITY OF SCIENCE TEACHERS UNDER THE KAMPHAENG PHET PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Panya, Panya; Lalitpasan, Usanee; Tanak, Akarat (Journal of Education and Innovation, 2025)
The goal of this research is to examine science instructors’ proficiency in learning assessments and to evaluate the needs for developing science teachers’ learning assessment competency. The sample consisted of 166 science teachers from Kamphaeng Phet Primary Educational Service Area Office 2, selected through stratified random sampling. Data was collected using a dual-response format questionnaire with a 5-point rating scale. Content validity was verified by three experts (IOC = 0.67-1.00), and reliability was assessed using Cronbach’s alpha coefficient (α=0.96). Data analysis employed frequency, mean, standard deviation, PNImodified, and matrix analysis. The findings showed that science teachers under the Office of Kamphaeng Phet Elementary Education Service Area Office 2 demonstrated a high level of learning assessment competency, including Assessment of Learning (M=3.89, SD=0.73), Assessment for Learning (M=3.86, SD=0.76), and Assessment as Learning (M=3.77, SD=0.77) are all demonstrated. The highest need for assessment of science teachers was assessment as learning (PNImodified = 0.17), followed by assessment for learning (PNImodified = 0.16) and assessment of learning (PNImodified = 0.15), respectively. In detail, the highest need for assessment as learning is assessment design based on actual conditions in which learners participated in the assessment design (PNImodified = 0.27), followed by the use of assessment results to improve learners’ learning and the use of assessment to improve teacher teaching during and after teaching by students’ self-reflection (PNImodified = 0.26) and the use of assessment results to improve learners’ learning and the teaching of teachers after the end of teaching where students self-reflect with the presentation of the report on the preparation of the learning assessment design project after the end of teaching (PNImodified = 0.21).